1999
DOI: 10.1136/bjo.83.3.339
|View full text |Cite
|
Sign up to set email alerts
|

AIDS related eye disease in Burundi, Africa

Abstract: Aims-To determine the prevalence of ocular manifestations in AIDS patients hospitalised in Bujumbura, Burundi, according to their CD4+ lymphocyte count, serological status for CMV and VZV, and general health status. Methods-Prospective study of 154 consecutive patients who underwent general and ophthalmological examinations, including dilated fundus examination. AIDS was diagnosed on the basis of Bangui criteria and HIV-1 seropositivity. CD4+ lymphocyte counts were determined by the Capcellia method. CMV and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 25 publications
3
34
1
Order By: Relevance
“…Studies carried out in Burundi and Malawi have revealed a prevalence of HIV-/AIDS-associated ocular manifestations of 19% and 20%, respectively. 12,14 Another Nigerian study, carried out by Kehinde et al, reported HIV-/ AIDS-associated ocular manifestations in 12.3% of their study population. 23 In a similar study conducted in India among HIV/AIDS patients on HAART, only eight per cent of the study population had ocular manifestations of the disease.…”
Section: Hiv-/aids-associated Ocular Manifestationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies carried out in Burundi and Malawi have revealed a prevalence of HIV-/AIDS-associated ocular manifestations of 19% and 20%, respectively. 12,14 Another Nigerian study, carried out by Kehinde et al, reported HIV-/ AIDS-associated ocular manifestations in 12.3% of their study population. 23 In a similar study conducted in India among HIV/AIDS patients on HAART, only eight per cent of the study population had ocular manifestations of the disease.…”
Section: Hiv-/aids-associated Ocular Manifestationsmentioning
confidence: 95%
“…10 The patterns of ocular diseases in HIV-infected patients in developed countries differ from those in developing countries. 8,11,12 Antibodies against cytomegalovirus (CMV) are detectable in 90% of people living with HIV-AIDS, but CMV retinitis is rare (< 5%) in…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of oral and esophageal candidiasis ranged from 14% in pregnant women with HIV [81] to 67% of Senegalese inpatients with AIDS [22,24,82,83]. Incidence rates are presented in table 2 [30,31,38].…”
Section: Neoformansmentioning
confidence: 99%
“…tuberculosis. Tuberculosis was diagnosed in 27%-34% of consecutive HIV-1-infected patients admitted to hospitals in Kenya [21] and South Africa [22], 39% of rural Tanzanians presenting with respiratory symptoms [23], and 61% of Burundian patients with AIDS [24]. Tuberculosis was diagnosed by smear or culture of a sputum sample and/or bronchoalveolar lavage or transbronchial biopsy in 23% of smear-negative Rwandan patients [25], 27% of inpatients in Burundi [26], 51% of patients in a respiratory ward in Abidjan [27], and 69% of highly selected patients in Tanzania [28].…”
Section: Mycobacterial Infectionsmentioning
confidence: 99%
“…Published work is uneven and inconsistent, particularly with regard to Africa, 31,32,34,38,39 for reasons that remain unclear. Studies are diffi cult to compare because of diff erences in design, patient population, and reporting of HIV status.…”
Section: Personal Viewmentioning
confidence: 99%